The Sistem Asistif bagi Mahasiswa Berkebutuhan Khusus dalam Media Pembelajaran LENTERA di UIN Alauddin Makassar - Nari, Ridwang; Afif, Nur; Indra Syahyadi, Asep; Saputra, Wahyuddin; Syafii Qur'ani, Muhammad (Jurnal INSYPRO (Information System and Processing), 2023)
Education is a right of every individual. It's already listed in the laws of our country. Not only for those who have normal conditions, but also for those with limitations. The limited intellectual ability of children suffering from tuberculosis brings problems to their difficulty in attending academic lessons especially in higher education. The main problem that para-Dosen encountered was the problem of language in terms of its function as a medium of communication. Teachers have a hard time explaining to students who suffer from bullshit without using translator media to help get information from teachers to students with special needs. Nowadays, in the era of technological development and the post-Covid-19 pandemic, where learning is done online and offline, it's a new problem for students who have limited access to college lectures. Based on the existing facts, almost all colleges use online learning media, especially those that are in the shadow of the Ministry of Religion. The purpose of this research is to provide facilities in the form of an assistive system in the application of LMS LENTERA to students who suffer from bullshit in communicating and pursuing education so that education can be equal for the entire Indonesian people without discrimination of each other. The result of this research is the application of a sign language translator that is synchronized with Lentera's online learning media so that it is easier for the lecturer to communicate to students with special needs and also to students who want to convey their opinions to their lecturers